International organization and global governance - Weiss, Thomas G. (Thomas George), 1946-; Wilkinson, Rorden, 1970- (Routledge, Taylor & Francis Group, 2014)
"Featuring a strikingly diverse and impressive team of authors, this is the most comprehensive textbook available for courses on international organizations and global governance. This book covers the history, theories, structure, activities and policies of both state-centred institutions, and non-state actors in global politics"--